The Impact of children on household consumption structure in China - Zhong, Ruixi; Burlakov, Georgi; Čermáková, Klára; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
Entering 21st century, China facing severe population issues, who has continuously adjusted its fertility policies. However, it still hard to change the situation, population issues and family consumption habits have become obstacles for expanding domestic demand and promoting economic development. Therefore, studying family consumption from the perspectives of the number and gender of children can promote a dual enhancement of fertility and consumption, which is beneficial for fostering a virtuous cycle of population and economic development. This study first summarizes and analyses the effects and mechanisms of the number and gender of children on household consumption at a theoretical level. Then it analyses the current situation of fertility and consumption in China. Finally, using the 2019 China Household Finance Survey (CHFS) data as a sample, an OLS model is used, with the number of children and gender as independent variables, and total household consumption and consumption structure as dependent variables, respectively. The study also takes a series of factors such as family characteristics and parental characteristics as control variables. The empirical results indicate that, firstly, when the number of children is three or fewer, the number of children promotes total household consumption expenditure. But for different consumption categories, there is no significant influence. Secondly, families with boys have lower total consumption expenditure (excluding housing consumption) compared to families with girls also with relatively higher spending on housing expenditure. However, for families with girls, clothing consumption expenditure will be relatively higher. Based on the empirical results, three suggestions are proposed. Firstly, family income levels should be increased to enhance the total household consumption budget. Secondly, correct consumption ideas should be consistently promoted to drive consumption upgrades.
Thirdly, educational reform should be strengthened to reduce the cost of children's education for families.
Vedoucí práce: Georgi Burlakov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses